Trends in Scientific Research Publications in Scopus from The Islamic Perspective - Mahfooz Ahmed; Rosalina Othman; Akram M Z M Khedher (Universiti Sains Islam Malaysia, 2025)
Sains Insani, Volume 9 Issue 2 Page (354-361)